Effect of lighting on starfruit's grading process [electronic resource] - Mohd. Kamal Abdul Kadir, 1987-, author; Syed Abd. Rahman Al-Attas, supervisor; Fakulti Kejuruteraan Elektrik (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mikroelektronik)) - Universiti Teknologi Malaysia, 2011